The Use of E-Lkpd Google Slide Assisted Pear Deck to Improve Students Concept Understanding on Ecosystem Material - Jannah, Miftahul; Hasni; Supriatno, Bambang; Hamdiyati, Yanti (Bioilmi: Jurnal Pendidikan, 2024)
Concept understanding is an important ability that students must have in the learning process, based on previous research, the understanding of the concept of students, especially in ecosystem material, is still relatively low, this is because the appropriate learning media has not been integrated. This study aims to improve students' understanding of concepts in ecosystem material by using google slide LKPD assisted by pear deck. This research method uses a pre experimental design with a one-group pre-test post-test design and the sample is taken by convenience sampling technique. The instruments used were test questions and questionnaires. Analysis of research data includes descriptive statistics and N-Gain test. Based on the results of the concept understanding test data analysis, the average percentage of students' concept understanding increased from 37.5% in the low category to 77.81% in the high category. The results of inferential statistical analysis using N-Gain obtained an average of 0.64 with a moderate category. It can be concluded that the use of E-LKPD google slide assisted pear deck can improve students' concept understanding on ecosystem material.